ANALISIS TIME SCHEDULE PADA PROYEK PEMBANGUNAN GEDUNG KANTOR KPU MAJALENGKA - Resy Usfuriya; EKA JULIAR (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
In a project, the role of the time schedule is very important in the implementation of the project because it is necessary to manage the time for the project to be carried out in accordance with the targets to be achieved and as a guide in the implementation of the construction stages so that the project can be carried out properly without any obstacles. If in a project there is no time schedule, then the project cannot be managed properly and the results are not optimal or the implementation may exceed the project time limit. Therefore, the time schedule is a very important part of a project. Time schedule analysis is carried out using weekly data in the form of an S curve and a description of the implementation to determine problems that occur in the field and solutions to these problems.